Peran Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Bekasi dalam Memenuhi Kota Layak Anak di Kota Bekasi - Susianti, Eka Putri; Rahayu, Susi Dian (IQTIDA : Journal of Da'wah and Communication, 2024)
This research aims to explore the role of the Women's Empowerment and Child Protection Office in fulfilling the Child Friendly City in Bekasi City. The research method used is qualitative with a case study, namely the Child Friendly City Program since 2013 with the Nindya Predicate in 2022. Data collection using interviews, observation, and literature study. The results of this study indicate that the role of the Office of Women's Empowerment and Child Protection in fulfilling child-friendly cities in Bekasi City consists of 3 roles, namely Active Role, Participatory Role and Passive Role. In active and participatory roles, there has been a decrease in the predicate in the Child Friendly City assessment. In 2019-2022, the Bekasi City Women's Empowerment and Child Protection Office managed to get the Nindya predicate, but in 2023 it fell to the Intermediate rank. Obstacles faced in fulfilling Child Friendly Cities include violence against children in the school environment, rampant cigarette advertising, lack of communication between the Bekasi City Women's Empowerment and Child Protection Office and the Child Friendly City Task Force Team and child exploitation.